PENGEMBANGAN PROFESIONALISME GURU - ABBAS Abbas (Adaara: Jurnal Manajemen Pendidikan Islam, 2018)
Abstract. This article discusses the development of teacher professionalism. Teachers as professional educators must have the ability (skill) in managing these activities effectively and efficiently. The task and role of the teacher is not limited in the community, even the teacher is essentially a strategic component that chooses an important role in determining the progress of the nation's life. Even the existence of the teacher is a sine quanon condisio that cannot be replaced by any component in the life of the nation since long ago, especially in this contemporary era. Therefore there needs to be an effort that must be done to develop teacher professionalism. Keywords: Development Of Teacher Professionalism